THE SPIRIT AND THE ACADEMY - Williams, David T. (2005)
The lack of interest, even rejection, of the intellectual study of Christianity by Pentecostals and their related movements is not a new feature. On the other hand, their stress on the direct experience of the Spirit has often been derided as irrational. However, the intellectual and "spiritual" must be fundamentally compatible, even complementary. This means that academic study can enhance spiritual growth, and at the same time the nature of the Spirit is such that he can well significantly help the understanding, development and communication of intellectual theology.